The Hidden Value of Adult Informal Care in Europe - Joan Costa-Font; Cristina Vilaplana-Prieto (CESifo GmbH, 2024)
The hidden value of adult informal care (IC) refers to the unaccounted value of informal care in overall costs of long-term care (LTC) estimates. This paper estimates the net wellbeing value of adult IC in Europe, drawing on a wellbeing-based methodology. We use an instrumental variable strategy and a longitudinal and cross-country dataset to estimate the causal effect of the extensive and intensive margin of caregiving on subjective wellbeing. Finally, we estimate the so-called compensating surplus (CS), namely the income equivalent transfer to compensate for the net disutility of caregiving. We find that IC reduces average subjective wellbeing by about 1% compared to the mean (6% among co-residential caregivers). Relative to a country's Gross Domestic Product (GDP), the value of informal care ranges between 4.2% in France and 0.85% in Germany, which is inversely correlated with the country's share of formal LTC spending and leads to reconsidering LTC regimes. The average CS per hour of IC ranges between 9.55 exteuro/hour, ranging between 22 exteuro/hour in Switzerland and 5 exteuro/hour in Spain. Finally, we also find that long-term CS is smaller than short-term CS.
Keywords: I18; J17; J18; 330; informal care; wellbeing methods; the value of time; caregiving; daughters; life satisfaction